Synthesis and Optical Properties of Carbon Quantum Dots Based on Terung Dayak (Solanum Ferox) Fruit Juice as Antioxidant and Metal Ion Sensor - Mokhamat Ariefin; Marvin Horale Pasaribu; Tety Wahyuningsih Manurung; Muh. Supwatul Hakim; Elvina Dhiaul Iftitah; Joy Angel Aria Suma; Risfiah Ruli Cahyani (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Carbon dots (CDs) are a novel class of carbon-based nanomaterials with diverse applications due to their biocompatibility, optical properties, and chemical stability. This study aims to synthesize CDs from Terung Dayak (Solanum ferox) using a microwave-assisted method and evaluate their optical properties, metal ion sensing capability, and antioxidant activity. The CDs were synthesized with variations in microwave power and citric acid concentration, specifically: CD-a using 1 g citric acid at 600 W, CD-b using 2 g citric acid at 600 W, CD-c using 3 g citric acid at 600 W, and CD-d using 2 g citric acid at 800 W, and then characterized using UV-Vis and fluorescence spectroscopy. The results revealed strong UV absorption with maximum peaks at 250 nm for all CDs synthesized and 275 nm for CD-d, depending on synthesis conditions. The CDs exhibited fluorescence intensity influenced by microwave power, with the highest intensity observed for CDs synthesized at 800 W and 2 g of citric acid. The optical bandgap from UV-Vis spectra, determined via Tauc plot analysis, ranged from 4.03 eV to 4.71 eV, indicating quantum confinement effects for all CDs. Furthermore, CD-d demonstrated selective fluorescence quenching for Fe3+ ions, which quenched the fluorescence of the CD. Antioxidant activity was confirmed via 2,2-diphenyl-1-picryhydrazyl (DPPH) radical scavenging, with an IC50 value of 126 ppm for CD-d. These findings highlight the potential of Terung Dayak-derived CDs as multifunctional materials for sensing and antioxidant applications.